Cortico-basal ganglionic degeneration a case report - J. Teotônio de Oliveira; Francisco E. Cota Cardoso (Arquivos de Neuro-Psiquiatria)
The case of a Brazilian patient with cortico-basal ganglionic degeneration (CBGD) is presented. Since three years ago, a 71-year old male displays asymmetric ideomotor apraxia, gait apraxia, cortical sensory impairment, myoclonus, limp dystonia and rigidity. His mental status is spared. There is neither consanguinity nor similar cases in his family. The differential diagnosis of CBGD is discussed. A brief review of the literature is made stressing the clinical and pathological features of CBGD. This disease is poorly known and probably underdiagnosed. Its diagnosis can be safely made based on clinical grounds.